Relationship between comprehensive vocabulary and early mathematical competence in 5- and 6-year-old children - Yaringaño Limache, Juan José (2017)
The objective of this study is to determine the relationship between comprehensive vocabulary and early mathematical competence. A type of correlational descriptive research is sought, being the sample of subjects constituted by 45 children of a state educational institution. The results indicate that there is a significant correlation between the comprehensive vocabulary and early mathematical competence (Rho = .617), in addition to having a rela-tionship between the comprehensive vocabulary and the relational capacity component (Rho = .661) and the numerical component (Rho=. 441). These results allow us to conclude that the comprehensive vocabulary associated with spatial, quantitative, temporal, qualitati-ve concepts of size and form, are related to the mathematical competence of the number.